Marrying in South Asia: Shifting, concepts, changing practices in a globalising World - Kaur, Ravinder; Palriwala, Rajni (New Delhi Orient Blackswan, 2018)
Marrying in South Asia looks closely at the changing notions and practices of marriage in Bangladeshi, Pakistani and south Indian Muslims, Bhutanese ethnic groups, Nepali widows, the Sri Lankan Tamil diaspora, south Asian gays and lesbians, middle class and urban, working class communities, and many other groups. With the globalising world as the backdrop, the essays in this volume examine the processes that make a marriage.